Knowledge, Attitude and Practice (KAP) Towards Safety Harness Usage Among Workers While Working at Height In A Low-Rise Construction Site - Nor Atiqah Marsya,; Sahak, Nurrul Hafeezah; Muhamad Firdous, (Progress in Engineering Application and Technology, 2023)
In the 2000s, construction in Malaysia rapidly expanded. The use of foreign labor in Malaysia's construction sector is extremely prevalent. In Malaysia, laborers from Bangladesh, Nepal, Indonesia, and the Philippines are frequently hired. Undoubtedly, unsafe behavior and a poor safety culture are to blame for the fact that Malaysian construction safety performance has not improved. Workers' awareness of safe behavior varies, and the social effects were tied to workers' productivity, social well-being, including safety and health. The ideas of safety behavior and safety culture as they are used in the Malaysian construction sector are not well understood due to a lack of consistent inspections. The aim of this study were to determine the level of knowledge, attitude and practice towards safety harness usage among workers at construction site and to determine the statistical different of socio-demographic factors (age, nationality, work experiences) on knowledge, attitude and practice of using safety harness among workers at construction site while working at height. Plus, to recommend good safety practices of using safety harnesses among workers while working at height. The research method used for this project is the questionnaire form. The collection of data and findings from the questionnaire are analyzed using descriptive data analysis and a one-way ANOVA test. Insights gained from this study will allow for the identification of worker knowledge, attitude, and practice regarding safety harnesses when working at height, as well as the promoting a best safety practices. The findings of this study highlighted there is a significant between knowledge and practices toward age group and work experiences, meanwhile there is no significant between attitudes and the nationality of workers. The foreign workers need to be provided with the appropriate training so that it can align with their knowledge and practice towards safety harnesses usage while working at height.